The Impact of Effective Talent Management Practices on Market Capitalizing Agility, Agile Innovation and Agile Creativity: a Quantitative Study in Knowledge-based Organizations - AL ALI, ALANOUD ABDULLA JUMA ALHAJ (2024)
Talent Management practices conceptualization captured considerable attention in the literature since the evolvement of the concept in the early 1990s, however, less attention has been given to empirical studies on the impact of Talent Management practices on organizational competitiveness. This empirical study considers the impact of effective talent management practices on competitive organizational agility (market capitalizing agility, agile innovation, and agile creativity) directly and through the mediating effects of operational adjustment capacity and absorptive capacity. The research population is knowledge-based organizations in the private sector. The findings presented are based on a deductive quantitative research design utilizing a positivist approach through deploying a cross-sectional survey. Responses to the survey were collected at an organizational level. Organizations in the UK were targeted with a sample size of 314. Data were analyzed through a Partial Least Square approach to Structural Equation Modeling (PLS-SEM) using smartPLS version 4. The present study addresses multiple gaps existing in the literature. The findings indicate a statistically significant positive relationship between effective talent management practices and agile innovation, agile creativity, operational adjustment capacity, and absorptive capacity. Also, the findings indicate that the relationship between effective talent management practices and market capitalizing agility, agile innovation, and agile creativity is mediated through absorptive capacity. Furthermore, the relationship between effective talent management practices and market capitalizing agility and agile creativity is mediated through operational adjustment capacity. To the best of the researcher’s knowledge, this is one of the first studies that attempted to quantitatively investigate these relationships.